ANALGESIC EFFICACY OF COMBINED SERRATUS ANTERIOR PLANE BLOCK AND INTRATHORACIC THORACIC PARAVERTEBRAL BLOCK IN VIDEO-ASSISTED THORACIC SURGERY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the intraoperative anesthesia efficacy and postoperative analgesic effect of combining a pre-induction serratus anterior plane block (SAPB) with an intrathoracic thoracic paravertebral block (TPVB) performed before chest closure in video-assisted thoracoscopic surgery (VATS).Methods: A clinical interventional study was conducted on 30 patients who underwent VATS at Viet Duc University Hospital.The SAPB was performed pre-induction under ultrasound guidance, followed by intrathoracic TPVB performed by the surgeon under direct thoracoscopic visualization before skin closure.Onset time, extent of sensory block, duration of analgesia, intraoperative fentanyl consumption, and postoperative morphine requirements via patient-controlled analgesia (PCA) were recorded and analyzed.Results: The onset time was 5.13 ± 0.73 minutes; the sensory block circumference was 56.23 ± 8.32 cm; and the total duration of the combined SAPB + TPVB effect was 516.83 ± 23.36 minutes. The intraoperative fentanyl consumption was 108.33 ± 18.95 µg. Postoperative VAS scores at rest, during movement, and on coughing remained low immediately after surgery, increased slightly within the first few hours, then gradually decreased and stabilized at low levels up to 72 hours postoperatively. Morphine consumption via PCA: total dose at 24 hours was 23.50 ± 3.98 mg; at 72 hours, 34.76 ± 3.86 mg. The time to the first “rescue” dose was 431.0 ± 18.82 minutes, and the number of unsuccessful demand attempts was 6.37 ± 0.49. Conclusion:The combination of pre-induction SAPB and intrathoracic TPVB before chest closure provided adequate intraoperative anesthesia,and ensured effective and sustained postoperative analgesia for up to 72 hours, with low morphine requirements in VATS patients.
Keywords: Serratus anterior plane block; thoracic paravertebral block; video-assisted thoracoscopic surgery; postoperative analgesi; morphine PCA (patient-controlled analgesia)